Kant on the Role of Religion for Moral Progress. Issue 3 (September 2019) - Buddeberg, Eva
Abstract: This article examines Kant's understanding of moral progress, especially in his Religion where he argues that religion and, more importantly, the foundation of an ethical community are necessary to promote moral progress. However, it is less the identification of any factual moral progress but rather the idea of moral progress as an action guiding principle that Kant identifies as central. The conclusion shows how Kant's insights are in accordance with the argument that we should not look for comprehensive moral progress in history but adhere to the idea of possible future moral progress.